Dalang Anak dalam Pakeliran Wayang Kulit Purwa Gaya Surakarta - Junaidi - (Institut Seni Indonesia Yogyakarta, 2010)
Young Puppeteers on Solonese Wayang Performance. The aim of these research are to identify the structureof story, shadow puppet forms, and young puppeteer’s motivations in pakeliran of Surakartanese purwa shadowpuppets. This research applies multidiscipline approach, encompassing puppetry dramaturgy, iconography,physiognomy, and ethnochoreology, in order to study the stories, shadow puppets, and motivations. The pakeliranof purwa shadow puppets by young puppeteers performed in short time, short structure, skillful technique, andchildish characteristic are a puppetry learning medium for children, appreciation of puppetry since early ages, andan effort of future art life continuity. In addition, the motivation of young puppeteer tends to be intrinsic which isbased on the pleasant feeling in conducting non-commercial and profane activity.